Implementation Barriers and Socio-Economic Implications of Nepal's Revised Seismic Building Codes: Evidence from Municipalities in PGA 0.35g Zones - Sandesh Sigdel (Institut Teknologi Sepuluh Nopember (ITS), 2026)
Nepal's revised building codes NBC 105:2020 (Seismic Design of Buildings in Nepal) and NBC 205:2024 (Ready-to-use Detailing Guideline for low rise RC Building without masonry infill) represent critical advances in seismic safety following the devastating 2015 Gorkha earthquake. This study provides the first comprehensive multi-municipal assessment of implementation barriers and socio-economic impacts across five municipalities in Peak Ground Acceleration (PGA) 0.35g zones. Using mixed-method research combining surveys of 245 construction professionals, cost analysis of 30 building projects, and quality assessments, we quantify implementation challenges and their economic implications. Our findings reveal substantial technical expertise gaps, with only 31.83% of respondents demonstrating adequate code awareness. Construction costs increased by 10.98% (NPR 3,160 to NPR 3,505 per sq ft), while training quality directly correlates with compliance rates (90% for comprehensive training vs. 50% for minimal training). We recommend differentiated regulatory frameworks distinguishing residential and commercial construction requirements, coupled with targeted capacity building programs. These evidence-based insights inform policy interventions to balance seismic safety enhancement with construction sector viability in earthquake-prone developing regions.